The interaction of radiation with the gravitational field - B. V. Аlexeev; I. V. Ovchinnikova (Тонкие химические технологии, 2015)
Nonlocal relativistic hydrodynamic equations describing the motion of photons in a gravitational field are derived. Numerical self-similar wave solutions of these equations for one-dimensional motion of photons of the same energy in a longitudinal gravitational field are found. The influence of the gravitational field on the frequency and number of photons per unit volume is considered.